The Content Validity: Multiple Choices Complex Physics Instrument to Measure Critical Thinking Skills - Bhakti, Yoga Budi; Arthur, Riyan; Supriyati, Yetti (STKIP Singkawang, 2024)
This research is part of the development of critical thinking skills instruments in physics lessons for eleventh-grade high school students. In this section, the purpose of this study is to analyze the content validity of the instrument. The instruments developed consist of 20 multiple-choice questions constructed based on indicators of critical thinking skills, namely interpretation, analysis, evaluation, inference, and explanation. Furthermore, this instrument was assessed qualitatively and quantitatively by 6 experts with assessment aspects including: 1) The questions fit the CTS indicator, 2) The stimulus/stem fits the questions, 3) The questions are clearly formulated, and 4) The problem description is clear and unambiguous.The method used in this research is a descriptive analysis method for content validation based on Aikens' Formula. Data for content validation were obtained from 9 experts, comprising 6 lecturers and 3 physics teachers from high schools in Jakarta. Based on the results and discussion, it can be concluded that 20 items of the complex multiple-choice test instrument to measure the critical thinking ability of eleventh-grade high school physics students are declared valid based on Aiken's Validity.